2014
DOI: 10.1016/j.ijnss.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of perceived stigma among people living with human immunodeficiency virus/acquired immune deficiency syndrome in Henan Province, China

Abstract: Acquired immune deficiency syndrome Human immunodeficiency virus Stigma a b s t r a c t Purpose: To investigate the level of and factors influencing perceived stigma and discrimination among people living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (PLWHA) in Henan Province. Methods: In total, 161 PLWHA from Zhengzhou and Zhenping were investigated using the Berger HIV stigma scale. Results: The mean Berger stigma scale score was 105.70 ± 15.20, indicating a middle stigma level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 13 publications
6
21
1
2
Order By: Relevance
“…Though, in the present study, it was observed that the level of education and monthly income was not significantly associated with the respondents' experience of discrimination and also, with respect to the level of education, this lack of association was similarly observed in a previous African study [17]. On the contrary, some other studies [19,20] reported that, low levels of education among respondents, appear to be protective against perceived stigma among people living with HIV. This also, was not consistent with a study done among HIV positive African-Americans, where it was observed that higher education was associated with low levels of perceived stigma [21].…”
Section: Discussioncontrasting
confidence: 70%
“…Though, in the present study, it was observed that the level of education and monthly income was not significantly associated with the respondents' experience of discrimination and also, with respect to the level of education, this lack of association was similarly observed in a previous African study [17]. On the contrary, some other studies [19,20] reported that, low levels of education among respondents, appear to be protective against perceived stigma among people living with HIV. This also, was not consistent with a study done among HIV positive African-Americans, where it was observed that higher education was associated with low levels of perceived stigma [21].…”
Section: Discussioncontrasting
confidence: 70%
“…From our findings, HIV-related stigma appears to be a concern in the Singapore population, with mean HIV-stigma scores across the various domains being generally higher than that reported by PLWHA in Sweden [18] and India [19]. In addition, TSS levels in the current study were higher than that reported by PLWHA in India and comparable to that reported by PLWHA in China [20].…”
Section: Discussionsupporting
confidence: 51%
“…There may be several reasons for this, including higher expectations by the more highly-educated and their peer groups that they should have been more aware of potential risks of transmission of HIV, as well as higher perceived stakes and societal pressures when considering disclosure of their seropositive status. A separate study conducted in China, utilizing the same HIV-related stigma scale, shows support for these findings, in that individuals with a higher education level who were infected with HIV through a route other than blood transfusions, reported higher levels of perceived HIV-related stigma [20].…”
Section: Stigma and Educational Levelmentioning
confidence: 75%
“…Algo similar se evidenció para el presente estudio donde la población masculina representa un 83,9% de la población total encuestada, así mismo, un estudio mexicano reportó que el 82.6% de los casos de SIDA en 2008 pertenecían al sexo masculino; lo que concuerda claramente con la población de este estudio (18) . El puntaje general de percepción de estigma de Berger en este estudio fue similar a lo reportado en un estudio realizado en Nigeria (19) donde la media de la escala fue de 99,5 , al igual que un estudio en Canadá (20) donde la escala de Berger abreviada de 20 ítems presentó una media de 49, y un estudio realizado en China (24) donde la media fue de 105,7 en la escala de Berger evidencia que la problemática del estigma en las personas que viven con VIH/SIDA no tiene fronteras, se evidencia en cualquier población y cultura, más en unas que en otras, pero se observa que está presente.…”
Section: Discussionunclassified